The scent of Neotinea orchids from Basilicata (Southern Italy). Issue 14 (15th July 2022) - D'auria, Maurizio; Lorenz, Richard; Mecca, Marisabel; Racioppi, Rocco; Romano, Vito Antonio; Viggiani, Licia
Abstract: The scent of Neotinea species has been performed by using solid-phase microextraction– gas chromatography– mass spectrometry (SPME–GC–MS). The scent of Neotinea ustulata showed the presence of 9-tricosene, 1-nonadecanol and heinecosane. The analysis of the scent of Neotinea tridentata gave α-ionone as the main component. The scent of Neotinea lactea showed the presence of pentadecane, heptadecane and isopropyl palmitate. Neotinea maculata showed the presence in the scent of 1-decene and ethyl dodecanoate. Graphical Abstract: UF0001